Virus infection pattern imprinted and diversified the differentiation of T-cell memory in transcription and function - Wang, Yuan; Mei, Xinyue; Lin, Zhengfang; Yang, Xiaoyun; Cao, Jinpeng; Zhong, Jiaying; Wang, Junxiang; Cheng, Li; Wang, Zhongfang (Frontiers in Immunology, 2024)
Memory T (Tm) cells are a subpopulation of immune cells with great heterogeneity. Part of this diversity came from T cells that were primed with different viruses. Understanding the differences among different viral-specific Tms will help develop new therapeutic strategies for viral infections. In this study, we compared the transcriptome of Tm cells primed with CMV, EBV and SARS-CoV-2 with single-cell sequencing and studied the similarities and differences in terms of subpopulation composition, activation, metabolism and transcriptional regulation.We found that CMV is marked by plentiful cytotoxic Temra cells, while EBV is more abundant in functional Tem cells. More importantly, we found that CD28 and CTLA4 can be used as continuous indicators to interrogate the antiviral ability of T cells. Furthermore, we proposed that REL is a main regulatory factor for CMV-specific T cells producing cytokines and plays an antiviral role.T cell immunization is considered to be a more conservative and long-lasting way to protect our body from viral infection than antibody does. However, the T cells primed by different viruses are quite different from each other. Therefore, a more detailed study on the heterogeneity of memory T cells that primed by different viruses is important for T cell based vaccines development. Here, based on scRNA-seq analysis, we pointed out the difference in subtypes, functions, metabolisms and transcriptional regulation among CMV, EBV and SARS-CoV-2 specific memory T cells. Our results provides a basic background knowledges for T cell vaccine studies in future.